INVESTIGATION OF THE WEB ANALYTICS ROLE IN IMPROVING THE EFFICIENCY OF THE ORGANIZATION`S PERFORMANCE - O. V. Demkina; N. G. Shalamova (Вестник университета)
Web analytics allows you to collect and analyze information about visitors of Internet resources.The main metrics, used in web analytics, have been considered in the article, including domestic organizations in various fields of activity. The issue of increasing the profitability of an organization based on improving the web analytics system, focused on three aspects, has been examined: analysis of user behavior, analysis of the organization’s performance results, and analysis of user satisfaction. To determine the state of web analytics in the organization, as well as its influence on the profitability of a company, a matrix of web analytics influence on the profitability of the organization based on the A. Koshik matrix, − has been developed.